Non-governmental organization interventions for sustainable community development in Pulau Mantanani, Sabah / Yasmin Rasyid - Yasmin, Rasyid (2019)
Sustainable community development efforts contribute to the operationalization of the 17 Sustainable Development Goals (SDGs). One of the key stakeholder and mobilizer of sustainable community development efforts is the non-governmental organization (NGO) sector. NGOs contribute to sustainable community development through the delivery of interventions that assist community to become self-reliant, empowered and eventually attain sustainable development. This case study research examines the contribution of four NGOs towards the realization of sustainable community development to the Bajau Ubian indigenous community in Pulau Mantanani by observing and classifying the roles, functions and intervention strategies of the NGOs over a three-year study period. The study also sought to evaluate the impact of the NGO interventions towards sustainable community development and identify the factors that influence the ability of the NGO interventions to provide long-term benefits to the indigenous community, after the NGO or donor exits. Using a mixed method research approach enhanced by the Participatory Action Research (PAR) approach, the research and analytical methods include observations, collective inquiries, interviews, semi-structured surveys and focus group discussions with the 14 NGO officers (from four NGOs) and 178 community beneficiaries. The findings revealed that NGOs classified as Third or Fourth Generation Strategies NGOs based on Korten’s Generation Strategies theory, contribute to delivering interventions that are more impactful compared to First and Second Generation Strategies NGOs. The evidence in this study also revealed that NGOs can also embody multiple roles and functions, and as such function as hybrid NGOs in which hybrid NGOs demonstrate the characteristics of having multiple strategies and approaches towards delivering interventions to address one or more, or a combination of multiple dimensions of sustainable community development. This demonstrated that efforts for sustainable community development are multidisciplinary or interdisciplinary. This finding challenges Korten’s Generation Strategies’ theory in that the NGOs in the study revealed a non-linear evolution of NGO roles, functions and strategies over a temporal scale. Through the PAR-enhanced methodology, three key factors were identified to have a strong influence on the impact of the NGO interventions in providing sustained benefits to the community. These factors are (a) community capacity, assets and access, (b) NGO organizational and management approach, and (c) external factors such as politics, donors and the socio-cultural environment. The PAR-enhanced research approach, with its values and limitations, demonstrated the robustness of this methodology in its application to study the roles and impacts of NGO interventions towards sustainable community development. In short, this thesis demonstrated that the roles and functions of NGO interventions contribute towards the realization of sustainable community development. Additionally, the application of the principles of PAR enabled an effective engagement which provided the researcher, the NGOs and the local community with in-depth knowledge and understanding of the multidisciplinary dimensions of sustainable community development, further supporting the research approach as a suitable research method for innovation and sustainable science studies.